Clinical characteristics of lip infantile haemangiomas and main risk factors for ulceration: an 8‐year retrospective study of 69 Chinese infants. (27th April 2020) - Yu, L.; Li, L.L.; Yan, P.; Deng, L.; Gan, X.L.; Yao, X.J.; Zhu, Z.H.; Zhang, T.D.
Abstract: Background: Infantile haemangiomas (IHs) involving the lip are of special concern because of the susceptibility of complications, including ulceration, obstruction and disfigurement. The available data for the relationship between their clinical characteristics and ulcerations are limited. Objectives: To describe the clinical characteristics of lip IHs and to evaluate the main risk factors for ulceration. Methods: A retrospective study was designed that included infants with lip IHs during an 8‐year period, the clinical data of participants were collected, and univariable and multivariable logistic models were used to determine the relationships between the clinical characteristics of lip IHs and ulcerations. Location, size and type were investigated as potential independent factors influencing the development of ulceration. Results: A total of 69 lip IHs were identified including 40 girls and 29 boys. Ulcerations were found in 37 (53.6%) lip IHs. Lip haemangiomas experiencing ulceration had a mean size (SD) of 3.49 (2.82) cm 2 compared with 1.08 (0.96) cm 2 for those without ulceration. Twenty‐eight (52.8%) of the 53 localized haemangiomas and 9 (56.3%) of the 16 segmental haemangiomas experienced ulcerations. Univariable analyses of all investigated factors revealed significant associations of location and size with increased risk of ulceration, and these significant associations remained after adjusting for sex and age [OR 8.61 (95% CI, 2.24–33.13) and 2.62 (95% CI, 1.46–4.72), respectively]. The duration before ulceration was between 4 and 70 days after the occurrence of lip IHs, with a median of 28 (19.41) days. Most ulcers occurred within 45 days of IH occurrence. Conclusions: Ulceration is a common complication of lip IHs at an earlier stage. A swollen with pale or bright crimson appearance of the lip IH surface could be an important signal of subsequent ulceration. Location of the IH on the lower lip and lip IH size are risk factors for the occurrence of ulceration.